Shopee: How Does E-commerce Platforms Affect Consumer Behavior during the COVID-19 Pandemic in Malaysia? - Wong, Khoon Xue; Wang, Yinghui; Wang, Ruting; Wang, Mengyao; Oh, Zi Jian; Lok, Yee Huei; Khan, Nawaz; Khan, Faijan (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2023)
Shopee is the largest e-commerce platform in Southeast Asia, continued to grow in Shopee users during the covid-19 outbreak. The Shopee platform not only facilitates consumers to purchase essential items during the pandemic, but it also assists sellers in showcasing their products and ultimately achieving online shopping success after offline stores were forced to close. Shopee provides a simple and convenient interface for customers to have a better online shopping experience. This study aims to examine how Shopee as an enormous e-commerce platform affects consumer behavior during the Covid-19 pandemic in Malaysia. A total of 100 Shopee users from Malaysia participated in this survey. The data is collected through an online questionnaire survey. The findings depicted that perceived usefulness is the most factor affected consumer behavior. Interestingly, we discovered that perceived price did not significantly influence consumer behavior. The findings provide new insights into user perceptions of Shopee and contribute to consumer behavior. Keywords: Consumer behavior, COVID-19, E-commerce, Malaysia, Perceptions, Shopee